A facile strategy to synthesize three-dimensional Pd@Pt core–shell nanoflowers supported on graphene nanosheets as enhanced nanoelectrocatalysts for methanol oxidation1. Issue 52 (4th July 2015) - Chen, Yi; Yang, Jia; Yang, Ying; Peng, Zhiyao; Li, Jinhua; Mei, Tao; Wang, Jianying; Hao, Ming; Chen, Yalin; Xiong, Weilai; Zhang, Liu; Wang, Xianbao
<x xml:space="preserve">Abstract</x> A water-based surfactant-free synthesis of three-dimensional porous Pd@Pt core–shell nanoflowers on graphene with substantially enhanced electrocatalytic activity was reported.